The Creation and Destruction of The Universe: Comparison of The Perspectives in Science and The Qur’an - Teuku Muhammad Hary Ramadhan; Mustanir Yahya; Safrida S; Sulastri Sulastri; A Halim (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: This paper aims to analyze the comparison of the concepts of creation and destruction of the universe from the perspective of science and the Qur'an, by analyzing some relevant literature. The majority of the literature used in this paper comes from the ScienceDirect database. The keywords used in the reference search were "Big Bang Theory", "Evolution of the Universe", and "Cosmology". The selection of references is based on the degree to which the source provides a thorough account of the universe's formation and destruction, as well as on the author's ability to grasp the language employed. Based on a review of some literature, there are similarities in terms used by Science and the Qur'an to explain the creation of the universe, but there are also differences not because the Qur'an is not able to explain scientifically, but because the Qur'an explains implicitly, not explicitly. Science has not been able to provide certainty about when the universe ends, as well as the Qur'an which is not written concretely. The comparison of the perspectives on the creation and destruction of the universe from science and the Qur'an offers a thought-provoking journey into the realms of reason and faith. While science provides a methodical and empirical understanding of the cosmos, the Qur'an offers a spiritual and metaphysical interpretation.Abstrak: Tulisan ini bertujuan untuk menganalisis perbandingan konsep penciptaan dan kehancuran alam semesta dari perspektif Sains dan Al-Qur’an, dengan menganalisis beberapa literatur yang relevan. Mayoritas literatur yang digunakan dalam makalah ini berasal dari database ScienceDirect. Kata kunci yang digunakan dalam pencarian referensi adalah “Teori Big Bang”, “Evolusi Alam Semesta”, dan “Kosmologi”. Pemilihan referensi didasarkan pada sejauh mana sumber tersebut memberikan penjelasan menyeluruh tentang pembentukan dan kehancuran alam semesta, serta kemampuan penulis dalam memahami bahasa yang digunakan. Berdasarkan ulasan terhadap beberapa literatur, disimpulkan bahwa terdapat persamaan istilah yang digunakan oleh Sains dan Al-Qur’an untuk menjelaskan penciptaan alam semesta, namun ada juga yang berbeda. Hal tersebut bukan karena Al-Qur’an tidak mampu menjelaskan secara ilmiah, namun karena kitab suci tersebut menjelaskan secara implisit, tidak eksplisit. Sains belum mampu memberikan kepastian tentang kapan alam semesta berakhir, begitu juga dengan Al-Qur’an yang tidak menuliskan secara konkrit. Perbandingan perspektif penciptaan dan kehancuran alam semesta dari sains dan Al-Qur'an menawarkan perjalanan yang menggugah pikiran menuju alam akal dan iman. Sementara sains memberikan pemahaman metodis dan empiris tentang kosmos, Al-Qur'an menawarkan interpretasi spiritual dan metafisik.